Organic Olive Oil Soap Prepared Via Saponification Method - Abd Rahman, Noor Syaza; Mohd Adnan, Raudah; Mohd Nazari, Afiq Syazwan; Sidek, Suhana (Multidisciplinary Applied Research and Innovation, 2022)
Domestic soaps sold in the market were found to be unsuitable for those with dry and sensitive skin problems. In this study, a production of olive oil handmade soap is attempted with the presence of glycerin and sodium hydroxide(NaOH) via a cold saponication process. The soap was then tested by three methods; by using Fourier-transform infrared spectroscopy(FTIR) result, determination of weight, and pH value. All three of these methods aim to ensure that the soap that has been produced is completely safe for use by the public. The performance of the soap in the last week in terms of weight (94.3g) and pH (8) was significant. Based on the composition and class of components in the soap, there are no harmful components resulted from the reaction between olive oil and NaOH. The pH value is also in a safe range (6-8) for use on human skin. If the pH value is too low or too high, it will erode the human skin layer and likely lead to skin cancer. The time taken needed for soap to stop losing weight increases as the water content in the soap changes and increases too. Based on all these studies, this soap was found to be ready for use in the sixth week. Therefore, it can be concluded that soap making based on the above three studies is important to produce high-quality soap so that humans are not exposed to dangerous health problems such as eczema besides making this soap eco-friendly.